Liquidity-profitability trade-off : is it evident among Malaysian SMEs? - Zainudin, Nasruddin (Universiti Utara Malaysia, 2006)
The purpose of this study is to empirically examine the relationship between liquidity and profitability on a sample of small and medium sized enterprises (SMEs) in the Malaysian manufacturing sector.Using the nonparametric spearman rank correlation coefficient analysis,the result reveals that there is a moderate positive association between liquidity levels.The same test is again employed to establish the association between the two variables, signifying that larger small firms tend to maintain higher liquidity levels.Finally,the Kruskal-Wallis test statistic was applied to investigate whether or not different industry sectors had different levels of liquidity. The outcome confirms that different industry sectors do have different of liquidity.